TRANSFORMASI MANAJEMEN PENDIDIKAN ISLAM DI ERA DIGITAL DALAM MENJEMBATANI IDEALITAS NILAI ISLAMI DAN REALITAS KELEMBAGAAN - Hendrizal, Hendrizal; Sumarni, Titin; Nopriadi, Nopriadi; Yuliandi, Tomi Desra; Sumiati, Cici; Munandar, Anhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Educational Management (IEM) plays a strategic role in developing educational institutions that excel not only in academic achievement but also in moral and spiritual values. However, the rapid advancement of globalization, digitalization, and increasing demands for professionalism have created significant challenges, leading to a gap between the ideal principles of Islamic educational management and its actual implementation. This article aims to analyze the paradigm of Islamic educational management from the perspectives of ideality and reality, identify the factors contributing to the existing gaps, and formulate strategies to strengthen management practices in Islamic educational institutions. This study employs a qualitative approach using a literature review method by examining various scholarly books, journal articles, and relevant academic sources. The findings reveal that, ideally, Islamic educational management emphasizes the principles of trustworthiness (amanah), justice, professionalism, accountability, and consultation (shura). In practice, however, many Islamic educational institutions continue to face challenges related to human resource quality, leadership effectiveness, curriculum integration, and the utilization of information technology in institutional governance. Therefore, a comprehensive transformation of Islamic educational management is required by integrating Islamic values with modern management principles to improve educational quality, institutional competitiveness, and responsiveness to contemporary challenges. Such transformation is expected to bridge the gap between ideality and reality while strengthening the contribution of Islamic education to the development of future generations.